State Ideology at Work: Suppression and Promotion of Linguistic Diversity in Nepal (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
The state’s monolingual policies and linguistic diversity are in conflictual relationships, pulling against each other. This paper explores historical practices of monolingualism in Nepal’s multilingual land and critically examines current constitutional provisions for the promotion of linguistic diversity. To this end, the study combined qualitative methods of document analysis and semi-structured interviews to examine the status and scale of linguistic diversity in policy documents, including past and present constitutions, and understand key stakeholders’ perceptions of Nepal’s past and present language policies and programs. Findings show that state ideology shapes language policies with its direct impact on the documentation of linguistic diversity. Deeming linguistic diversity as a threat to national unity, Nepal in the past practiced a one-language, assimilationist policy that privileged the Nepali language, marginalizing other languages. Despite recent constitutional provisions for the promotion of the nation’s linguistic diversity, languages other than Nepali are still struggling to have official status, principally due to the continuation of monolingual hangover and the lack of concerted planning and programs in strengthening historically marginalized languages. These findings are expected to contribute to minimizing policy-practice dissonance and framing viable policies for the management of linguistic diversity in multilingual contexts like Nepal.